Pengaruh komposisi terhadap ukuran butir lapisan nanokomposit CoFe2O4/PVDF dengan metode spin coating (The influence of composition to the grain size of the CoFe2O4 / PVDF nanocomposite layer by using the spin coating method) - Diana Putri; Yenni Darvina; - Ramli; - Yulkifli (Department of Physics – Universitas Negeri Padang UNP, 2019)
The study of nanocomposites have been done much by researchers. Nanocomposites is a mixture of nanoparticle powder consisting of two materials called matrix and filler. The filler used in this study is CoFe2O4 and the matrix is PVDF. This study advantageous for investigating the micro structure of CoFe2O4/PVDF nanocomposite layer. The micro structure to be is the size of crystals, the micro strains, the size of grains and the thickness of nanocomposite layers. It is a research experiment that uses variations in composition 10 ml : 10 ml, 10 ml : 20 ml, 10 ml : 30 ml. The characterization tools used were X-ray Diffraction (XRD) and Scanning Electron Microscope (SEM). XRD is used to get the corner of two theta and a half peak width (FWHM) from a layer of nanocomposite. SEM characterization gets to morphology of the surface and the thickness of nanocomposite layers. The thickness of a nanocomposite layer obtained is that 25.11 m, 29.81 m, and 35.51 m. Based of research already done, the more thickness of a nanocomposite layers the size of crystals and micro strains has also increased.